Operation and control methods of modular multilevel converters in unbalanced AC grids : a review - Li, Jinke (2020)
High-voltage direct current (HVdc) transmission systems based on modular multilevel converters (MMCs) are a promising solution for efficient bulk power transmission over long distances. As in grid-connected converters, the occurrence of grid-side faults is rather common, leading to imbalances and distortions of the ac-side voltages. Therefore, operation and control of MMC-HVdc systems under grid imbalances become of great significance in order to satisfy grid codes and reliability requirements of the system. The aim of this paper is to provide a comprehensive review of operation and control methods applied to MMC-HVdc systems with a specific focus on unbalanced ac-grid conditions. The methods are classified based on their main control targets that include ac-side power control, control of the circulating current, and dc-side power ripple suppression control. Special attention is given to the comparison of the different control methods and specific requirements under certain operating conditions that include grid, load, or internal imbalances.